Pengaruh Product Quality, Online Customer Review, dan Price Discount terhadap Impulse Buying pada Marketplace Shopee - Reytha Ulfa Nurqia Ginting; Dedy Ansari Harahap; Mochamad Malik Akbar Rohandi (UNISBA Press, 2023)
Abstract. With the presence of e-commerce among the public in buying and selling products to meet their daily needs easily, consumers experience a change in behavior from shopping directly to conventional stores to shopping through e-commerce. This has led to the growth of online shopping and an increase in impulse buying with some indications that product quality, online customer reviews and price discounts will be factors in consumers making impulse buying. So this study aims to find out how product quality is described, online customer reviews and price discounts at Shopee and to determine the effect of product quality, online customer reviews and price discounts on Shopee. This research is a type of research with quantitative methods. The sampling technique used is non-probability sampling, namely purposive sampling. The population in this study were consumers who had made a purchase at least once and obtained a sample of 220 people. The data analysis used is descriptive analysis using multiple linear regression analysis. The results of this study indicate that product quality partially has a significant effect on impulsive purchases, online customer reviews partially have a significant effect on impulse purchases, and price discounts partially have a significant effect on impulse buying. And simultaneously product quality, online customer reviews and price discounts have a significant effect on impulse buying. Abstrak. Dengan adanya e-commerce dikalangan masyarakat dalam menjual dan membeli produk untuk memenuhi kebutuhan sehari-hari secara mudah, membuat konsumen mengalami perubahan perilaku dari berbelanja secara langsung ke toko konvensional menjadi berbelanja melalui e-commerce. Hal tersebut menyebabkan pertumbuhan belanja online dan peningkatan pembelian impulsif dengan beberapa indikasi bahwa product quality, online customer review dan price discount akan menjadi faktor konsumen melakukan pembelian impulsif. Penelitian ini bertujuan untuk mengetahui bagaimana gambaran product quality, online customer review dan price discount pada Shopee serta untuk mengetahui pengaruh product quality, online customer review dan price discount pada Shopee. Penelitian ini merupakan jenis penelitian dengan metode kuantitatif. Teknik sampling yang digunakan adalah nonprobability sampling yaitu purposive sampling. Populasi pada penelitian ini adalah konsumen yang telah melakukan pembelian minimal 1 kali dan didapatkan sampel sebanyak 220 orang. Analisis data yang digunakan adalah analisis deskriptif menggunakan analisis regresi linear berganda. Hasil penelitian ini menunjukkan bahwa product quality secara parsial berpengaruh signifikan terhadap impulse buying, online customer review secara parsial berpengaruh signifikan terhadap impulse buying, dan price discount secara parsial berpengaruh signifikan terhadap impulse buying. Serta secara simultan product quality, online customer review dan price discount berpengaruh signifikan terhadap impulse buying.